Management of asymptomatic hyperuricemia: Integrated Diabetes & Endocrine Academy (IDEA) consensus statement. Issue 2 (March 2020) - Valsaraj, Rahul; Singh, Awadhesh Kumar; Gangopadhyay, Kalyan Kumar; Ghoshdastidar, Biswajit; Goyal, Ghanshyam; Batin, Masood; Mukherjee, Dibyendu; Sengupta, Upal; Chatterjee, Sanjay; Sengupta, Nilanjan
Abstract: Aim: The definition and management of asymptomatic hyperuricemia has been an area of controversy for many decades. Debate persists regarding the benefit of treating all cases of asymptomatic hyperuricemia and hence, unsurprisingly there are no clear clinical practice guidelines from our country. Participants: Ten members consisting of eminent physicians, endocrinologists, nephrologist and a rheumatologist were selected by the Integrated Diabetes & Endocrine Academy (IDEA) for a closed meeting with the aim to come to a consensus. Evidence: A literature search was performed using PubMed and Cochrane library following which published articles in indexed peer review journals were selected. Consensus process: Each participant voiced their opinion after reviewing the available data and a consensus was reached after three meetings by voting. Conclusion: Recommendations were made on important areas such as definition, investigation and management of asymptomatic hyperuricemia. Highlights: There are no clear clinical practice guidelines on management of asymptomatic hyperuricemia from India. Unnecessary investigation of serum uric acid for all patients with rheumatological symptoms should be discouraged. Urate lowering therapy are well known for its side effects however, new evidence showing benefit of therapy cannot be ignored. This consensus statement aims to lay down clear recommendations in the management of asymptomatic hyperuricemia.